Traffici commerciali e approdi portuali nella Sardegna meridionale Analisi dei contenitori da trasporto e dei contesti subacquei (III-VII secolo) - Soro, Laura (Archaeopress Publishing, 2022)
Traffici commerciali e approdi portuali nella Sardegna meridionale is a study of trade flows on the southern coast of Sardinia in Late Antiquity through underwater finds, amphorae analysis and hypothetical docking points. Underwater surveys along the southern coasts in recent years have allowed us to expand the information registry and have highlighted multiple examples of possible cargoes from wrecks, especially of heterogeneous types, as in Cagliari, Nora (Pula) and in the sea around Sulcis. In particular, the port of Cagliari featured on routes for goods transport and perhaps transhipment. The materials and contexts included in this work originated from throughout the Mediterranean area (South Italy-Sicily, Gaul, Baetica, Lusitania, North Africa, East Mediterranean). A further aspect of the volume concerns the analysis of the underwater archaeological contexts of amphora finds, with the aim of understanding the degree of exploitation of each coastal area and identifying hypothetical docking points, through an underwater, historiographic geomorphological approach. The study aims to increase knowledge of the role of southern Sardinia in Mediterranean trade. Through its central place in the Western Mediterranean the island has played a strategic role in shipping routes and goods exchanges and its resources undoubtedly influenced, directly and indirectly, the involvement of southern Sardinia in ancient marine traffic and commercial exchanges.